POISON PAGES - Dahl, Michael; Blanco, Martin (North Mankato, Minnesota : Stone Arch Books, 2018)
Some books so evil that they must be imprisoned deep underground, but when the Librarian tries to dispose of one vile volume, he risks being buried alive in an eerie tower that holds a legendary secret.
Keywords: Children's stories, English; English fiction